Studi Kondisi Sanitasi Dengan Kualitas Bakteriologis Depot Air Minum Isi Ulang di Kecamatan Panakkukang Kota Makassar - Ronny Ronny; Dedi Mahyudin Syam (HIGIENE: Jurnal Kesehatan Lingkungan, 2016)
Water and Sanitation in Indonesia is still low compared with other countries in Southeast Asia. Only 50% of the entire population of Indonesia who gain access to drinking water. For human drinking water is a major requirement. Given that the disease can be carried by water to humans when people use it, the main purpose berish water supply and sanitation for the people is to prevent water-borne diseases. Thus it is expected that more and more people with clean water coverage and sanitation, getting lower morbidity of these water-borne diseases. Enterprises drinking water station today's rapidly growing importance in the provision of drinking water affordable to the community.The purpose of this research is to determine the condition of the sanitary and bacteriological quality of drinking water stations Refill in District Panakkukang Makassar.This type of research is survey with descriptive approach, namely to determine the sanitary conditions and the quality of bacteriological station refill drinking water in Sub Panakkukang Makassar.Based on the research that has been done that sanitary conditions at the station refill drinking water Equator qualify with a value of 86. For the inspection of sanitary conditions at the station 3 Nur values obtained pemerikssaan 74 and the examination object number 38 did not qualify so the station 3 Nur is said to be not meet the health requirements. The results of the bacteriological quality inspection (MPN Coliform) at the equator station did not contain coliform bacteria that is said to qualify and for station 3 Nur coliform bacteria content is 15 or ineligible.From the discussion, it can be concluded that the sanitary conditions and the quality of bacteriology at the equator station to station eligible and ineligible 3 Nur sanitary conditions and bacteriological quality. Keywords: Sanitary Conditions, Bacteriological Quality, Drinking Water Station Refill